The Display of Islamic Conflictual Discourses through Logics of Film Discourse Interpretation (NOBEL: Journal of Literature and Language Teaching, 2023)
In the past few decades, Islamic discourse in Indonesia was turning more problematic, leaving some issues to the conflict between majority and minority discourses (the Muslims’ conception) of Islam. Some of the manifestations of discursive conflict were captured in popular work, such as the movie Ayat-Ayat Adinda. This research tries to unpack the movie using Wildfeuer's Logics of Film Discourse Interpretation (FDI) theory and combine it with the concept of Halliday's ideational metafunction to track the Islamic signs emanated by the movie. FDI is chosen to fill the area which has not been studied by previous research. This study found some rhetorical segment relations: Result, Elaboration, Contrast, Background, Parallel, and Narration, presenting two Islamic discourses being contested. However, the interesting point is indicated at the end of the resolution of the movie that none of the discourses wins. This study interpretation is somehow implicitly parallel to the spirit of 'moderation' of religion when the movie maker hopes that it can stop violence and discrimination which degrade religious practices in Indonesia.